Evolutionary implications of localization of the signaling scaffold protein Parafusin to both cilia and the nucleus. (28th July 2014) - Satir, Birgit Hegner; Wyroba, Elzbieta; Liu, Li; Lethan, Mette; Satir, Peter; Christensen, Søren Tvorup
Abstract Parafusin (PFUS), a 63 kDa protein first discovered in the eukaryote Paramecium and known for its role in apicomplexan exocytosis, provides a model for the common origin of cellular systems employing scaffold proteins for targeting and signaling. PFUS is closely related to eubacterial rather than archeal phosphoglucomutases (PGM) – as we proved by comparison of their 88 sequences – but has no PGM activity. Immunofluorescence microscopy analysis with a PFUS‐specific peptide antibody showed presence of this protein around the base region of primary cilia in a variety of mammalian cell types, including mouse embryonic (MEFs) and human foreskin fibroblasts (hFFs), human carcinoma stem cells (NT‐2 cells), and human retinal pigment epithelial (RPE) cells. Further, PFUS localized to the nucleus of fibroblasts, and prominently to nucleoli of MEFs. Localization studies were confirmed by Western blot analysis, showing that the PFUS antibody specifically recognizes a single protein of ca. 63 kDa in both cytoplasmic and nuclear fractions. Finally, immunofluorescence microscopy analysis showed that PFUS localized to nuclei and cilia in Paramecium. These results support the suggestion that PFUS plays a role in signaling between nucleus and cilia, and that the cilium and the nucleus both evolved around the time of eukaryotic emergence. We hypothesize that near the beginnings of eukaryotic cell evolution, scaffold proteins such as PFUS arose as peripheral membrane protein identifiers for cytoplasmic membrane trafficking and were employed similarly during the subsequent evolution of exocytic, nuclear transport, and ciliogenic mechanisms.